Respuesta :

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️

[tex]f(x) = 2 {x}^{2} - 7x - 7[/tex]

[tex]g(x) = x + 1[/tex]

_________________________________

[tex]f(g(x)) = 2 ({x + 1})^{2} - 7(x + 1) - 7 \\ [/tex]

[tex]f(g(x)) = 2( {x}^{2} + 2x + 1) - 7x - 7 - 7 \\ [/tex]

[tex]f(g(x)) = 2 {x}^{2} + 4x + 2 - 7x - 7 - 7 \\ [/tex]

Collect like terms

[tex]f(g(x)) = 2 {x}^{2} + (4 - 7)x - 14 + 2 \\ [/tex]

[tex]f(g(x)) = 2 {x}^{2} - 3x - 12 [/tex]

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️

Answer:

[tex]2x^{2} -3x-12[/tex]

Step-by-step explanation:

To solve composite functions, figure out which function is on the "inside" and the outside":

f(x) is the inside and g(x) is the outside

Now plug the value of g(x) into the x values of f(x):

[tex]2(x+1)^{2}-7(x+1)-7[/tex]

Then distribute following the steps of PEMDAS:

[tex]2(x^{2}+2x+1)-7x-7-7[/tex]

[tex]2x^{2} + 4x + 2 - 7x -14[/tex]

Then combine like terms:

[tex]2x^{2} -3x-12[/tex]